Serine/Threonine Protein Phosphatase 2A Regulates the Transport of Axonal Mitochondria - Heo, Keunjung; Basu, Himanish; Gutnick, Amos; Wei, Wei; Shlevkov, Evgeny; Schwarz, Thomas L. (Frontiers in Cellular Neuroscience, 2022)
Microtubule-based transport provides mitochondria to distant regions of neurons and is essential for neuronal health. To identify compounds that increase mitochondrial motility, we screened 1641 small-molecules in a high-throughput screening platform. Indirubin and cantharidin increased mitochondrial motility in rat cortical neurons. Cantharidin is known to inhibit PP2A. We therefore tested two other inhibitors of PP2A: LB-100 and okadaic acid. LB-100 increased mitochondrial motility, but okadaic acid did not. To resolve this discrepancy, we knocked down expression of the catalytic subunit of PP2A (PP2CA). This long-term inhibition of PP2A more than doubled retrograde transport of axonal mitochondria, confirming the importance of PP2A as a regulator of mitochondrial motility and as the likely mediator of cantharidin’s effect.